2022
DOI: 10.1128/spectrum.01617-21
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia fergusonii, an Underrated Repository for Antimicrobial Resistance in Food Animals

Abstract: E. fergusonii , a member of the genus Escherichia , has been reported to transmit via the food chain and cause diseases in humans. However, the prevalence of multidrug-resistant E. fergusonii , especially mcr-1 -positive E. fergusonii isolates, has rarely been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…These critical AMR genes in E. coli isolates from food animals present a tremendous public health concern. It’s important to mention that the acquired AMR genes in bacterial genomes do not inevitably confer phenotypic resistance and vice versa ( Boolchandani et al, 2019 ; Tang et al, 2022a ). Other mechanisms such as SNPs and MDRtransporter also significantly contribute to the phenotypic resistance ( Boolchandani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These critical AMR genes in E. coli isolates from food animals present a tremendous public health concern. It’s important to mention that the acquired AMR genes in bacterial genomes do not inevitably confer phenotypic resistance and vice versa ( Boolchandani et al, 2019 ; Tang et al, 2022a ). Other mechanisms such as SNPs and MDRtransporter also significantly contribute to the phenotypic resistance ( Boolchandani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent emergence and rapid increase of multi-drug resistant (MDR, resistance to more than three kinds of antibiotics) bacteria have caused public concern, represented by Escherichia coli resistant to carbapenem, colistin and tigecycline which were recognized as the last line of resort ( Li et al, 2017 ; He et al, 2019 ; Ma et al, 2022 ). Due to incorrect use and misuse of antibiotics, the spread of antimicrobial resistance (AMR) is accelerating ( Wang et al, 2022 ; Tang et al, 2022a , b ). The continuous spread of AMR not only increases the difficulty of preventing and controlling livestock and poultry diseases but also seriously threatens livestock products’ safety and endangers consumers’ health ( Xu et al, 2022 ; Li et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these last-resort antibiotics, colistin was heavily used in food-producing animal industries in China for a long period of time until it was banned as a growth promoter in 2017 ( Walsh and Wu, 2016 ). However, colistin-resistant Gram-negative pathogens, especially Enterobacteriaceae pathogens, still have high presence in poultry/livestock farm environments ( Liu et al, 2016 ; Tang et al, 2022 ), and the plasmid-borne resistance gene mcr-1 is the main factor contributing to widespread colistin resistance ( Arcilla et al, 2016 ). In addition, although the use of carbapenems, broad-spectrum β-lactam class antibiotics, is authorized only in clinics ( Ahmad et al, 2019 ; Farhat and Khan, 2020 ; Nasser et al, 2020 ), their main resistance gene, bla NDM-1 , is still frequently identified in Enterobacteriaceae pathogens in poultry/livestock farm environments.…”
Section: Discussionmentioning
confidence: 99%
“…As described in a previous study, the 11 E. coli strains were subjected to S1-PFGE to identify the number and size of plasmids [ 28 , 29 ]. The overnight cultures were washed with PBS buffer and then embedded in agarose plugs.…”
Section: Methodsmentioning
confidence: 99%